Active Non-Violence Education in Rural Culture: Religious Moderation Practices in Plajan Pakis Aji Jepara - Saefudin, Ahmad; Rohman, Fathur; Karwadi, Karwadi; Nasikhin, Nasikhin (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2022)
This article aims to describe a portrait of peace education involving three religions (Islam, Christianity, and Hinduism) in Plajan Village, Jepara Regency, Central Java. Also, to explain the practice of religious moderation through non-violent education implemented by the religious leaders there. Through a qualitative approach, the researcher observed the interaction between religious leaders to obtain data on the practice of religious moderation. Researchers conducted interviews with Kiai, priests, Hindu religious leaders, and village heads to reveal a portrait of non-violent education. Documentation is a complement to research data, especially in the form of a profile of Plajan village which is already known as a multicultural village. In conclusion, there are two values ​​of religious moderation practiced by religious leaders in Plajan Village, namely tasamuh (tolerance) and syura (deliberation). These two values ​​are in line with the concept of religious moderation initiated by the Ministry of Religion of the Republic of Indonesia. While the value of ukhuwwah basyariyyah, although outside the categorization of religious moderation from the Ministry of Religion of the Republic of Indonesia, is essentially in line with the value of islah (reform) and qudwah (pioneering).